Medieval paintings in the Dutch Reformed church at Britsum (Bulletin KNOB, 2000)
Between March 1998 and December 1999 decorative and figurative mural and vaultal paintings were exposed and restored in the Dutch Reformed church at Britsum. The decorative paintings were applied on the ribs of the vault, the transverse arches and around the figurative representations.They are geometric patterns and some ‘candelabra’. Parallels are to be found in churches in Westphalia painted under Westphalian influence at the end of the twelfth and in the first half of the thirteenth century. So far the figurative paintings only emerged in the zone directly below the vaults, mainly in the choir.The only vaultal painting is to be found on the most eastern panel of the vault of the nave and represents Mary with her son in her lap in a mandorla. The scenes in the choir were applied in pairs on an arch panel. They represent a passion cycle: Christ's Prayer on the Mount of Olives, the Betrayal of Judas, the Crowning with thorns and the Whipping.More is preserved of the Old-Testament figures in the spandrels of the arch panels: Abraham, Isaac, Jacob, Mozes, Aaron, Salomo with a viola, David with his harp. Jonathan, Absalom with a vielle and Saul. The iconographic special quality of the musical instruments seems to point to the influence of English Psalter illustrations, notably the Tree of Jesse, where from the late twelfth century onwards the ancestors of Christ are sometimes represented while playing music.The Old-Testament figures are probably typologically connected with the passion scenes; particularly the twelfth-century typological writing ‘Dialogus de laudibus sanctae crucis’ gives rise to such an assumption. Stylistic parallels tor the figures are to be found in the moderate ‘Zackenstil’, current in Lower Saxony and the environs of Cologne around the forties of the thirteenth century.Unique is the fact that the Crowning with thorns and the Whipping on the eastern wall of the choir form the focus of the cycle. Partly due to the prominent presence of Jews as enemies of the faith, the paintings at Britsum may be a reflection of the Frisian crusaders' enthusiasm in the mid-thirteenth century.